1962
DOI: 10.1086/267133
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the Impressions of Survey Interviewers

Abstract: Living Research is a section of the Quarterly reserved for brief reports of research, discussions of unsolved problems, presentations of neat methodological tricks, and other items that arise out of the daily work of researchers. It provides an opportunity for discussion in print of questions and results that may not seem to warrant a full-blown article. Researchers will find in this section a place to exhibit data which are not adequate to substantiate important generalizations but seem promising in their imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1974
1974

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…I doubt this for three reasons: ( 1 ) On the average, each worker interviewed eleven respondents, or three families, hardly enough to discover a trend; ( 2 ) In the two years that had elapsed prior to the reinterview, interviewers had probably forgotten. ( 3 ) Olmsted (1962) experimentally found that interviewing made no difference in the accuracy of interviewers' estimates of sample characteristics.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…I doubt this for three reasons: ( 1 ) On the average, each worker interviewed eleven respondents, or three families, hardly enough to discover a trend; ( 2 ) In the two years that had elapsed prior to the reinterview, interviewers had probably forgotten. ( 3 ) Olmsted (1962) experimentally found that interviewing made no difference in the accuracy of interviewers' estimates of sample characteristics.…”
Section: Discussion and Interpretationmentioning
confidence: 99%